Analysis of the levels of physical activity and body mass index of college students: a systematic review - André Filipe Morais Pinto Novo; Milena Oliveira Cardoso; Anderson Melo Chaves; Pâmella Reis de Abreu; Mariela de Santana Maneschy; Ricardo Pablo Passos; Bráulio Nascimento Lima; Guanis de Barros Vilela Junior; Klebson da Silva Almeida (Social Medicine Publication Group, 2021)
Background: The quality of life of college students is directly affected at the onset of college life due to the neglect of healthcare and predisposing risks such as obesity. Purpose: The main objective of the present study is to analyze the levels of physical activity and body mass index (BMI) of college students. Methods: The PubMed, Scielo, ScienceDirect, BVS, and Cochrane databases were selected. The search strategy included descriptors in English and Portuguese: "college students", "academics", "body mass index", "level of physical activity", and "quality of life". Results: After finding 16 articles, inclusion and exclusion criteria were applied, resulting in 10 articles for deep analysis. It was observed that college students had a good level of physical activity and adequate BMI, diverging from old studies in which the level of physical inactivity and overweight was relatively high. Discussion: From the studies carried out, it is concluded that currently college students are within normal weight and are physically active. Translation to Health Education Practice: Further studies about BMI and physical activity levels, as two important health indicators, should be carried out in college students.